Efeito do alongamento vaginal e da fotobiomodulação sobre a dor pélvica crônica e a função sexual de mulheres adultas: um protocolo de ensaio clínico - Souza, Rafaela Jéssica Silveira de (2024)
Introduction: Chronic pelvic pain (CPP) is a multifactorial condition affecting one in every six adult women, characterized by persistent pelvic pain associated with the genitourinary, gastrointestinal, and musculoskeletal systems. It is also related to sexual dysfunction and significant mood changes, directly impacting the reduction of quality of life. Stretching is a therapeutic alternative for restoring the functional integrity of the pelvic floor muscles. Concurrently, other strategies have emerged as effective alternatives to assist established protocols, among which photobiomodulation (PBM) stands out. PBM involves the emission of low-intensity light to promote modulation of the inflammatory process and tissue repair, providing analgesic effects on skeletal muscles and alleviating symptoms related to female sexual dysfunction (FSD) and CPP. Therefore, this study aims to analyze the association of stretching with PBM in the treatment of CPP and FSD.Methods:This is a prospective, randomized controlled clinical trial to be conducted by a specialized team from the Department of Physiotherapy at the Federal University of Rio Grande do Norte (UFRN), located in Natal, Rio Grande do Norte, Brazil. Female individuals aged 18 to 50 years, with active sexual lives, diagnosed with CPP and reporting sexual dysfunction complaints, will be recruited. Eligible patients for the study will be coded and randomized in a 1:1:1 allocation ratio into three groups: control group 1 (CG1) with stretching; control group 2 (CG2) with stretching and simulated intravaginal LED therapy; and the experimental group (EG) with stretching and active intravaginal LED therapy. Reassessments will occur after the 5th session, the 10th session, and at three and six months after the last session. Pain assessment will be measured using the Numerical Rating Scale, while sexual function will be evaluated using the Female Sexual Function Index (FSFI) questionnaire. The photobiomodulation device used will be the Fluence Maxx HTM®.Expected Results and Impacts:A positive outcome is anticipated in reducing the signs and symptoms of CPP and improving the sexual quality of life of patients, enabling the development of a standardized, safe, and effective protocol to be applied in both laboratory and clinical practice.